Social capital,economic performance and political engagement: A case study of Congolese Immigrants in Central Johannesburg - Mavungu, Mazembo (My University, 2007)
In this study, the positive correlation between social capital and economic performance as well as between social capital and political engagement, documented in the vibrant social capital literature, is revisited with focus on the experience of Congolese immigrants in Central Johannesburg. The core research question aims at establishing whether Congolese immigrants with higher stock of social capital turn out to be better economic performers and more politically engaged agents. The investigation has used both quantitative and qualitative methods. The major data collection instrument has been a survey questionnaire that has reached a relatively representative sample of 100 Congolese immigrants living in Yeoville, Berea, Hillbrow, Parktown, and Braamfontein. Informal interviews, direct observation, and previous literature has provided more qualitative information that has helped to account for statistical trends. While the Congolese immigrant community displays vibrant associational life and intensive social interactions, the predominance of religious associations, the scarcity of socio-economic organisations and the prevalence of bonding ties affect Congolese immigrants’ ability to benefit from their general high capacity to interact with others. The study has also found that voluntary associations may just have symbolic value as they do not represent support structures on which members rely to handle their daily challenges. Instead, family members and fellow Congolese friends constitute the most important social support. As for the correlation between social capital and economic performance, the model has been found valid but its explanatory power weak. Social capital can only partly account for Congolese immigrants’ economic performance. Its impact on their level of political engagement is equally weak. Social capital’s weak influence on Congolese level of political engagement has to do with the apolitical tendency of most religious associations, individuals’ lack of English proficiency, and poverty. South Africa institutional constraints to immigrants’ socio-economic integration, disempowering features of Congolese associations, individuals’ marginal position within networks and the general absence of resources have also been singled out as major justification of Congolese immigrants’ social capital powerlessness. This study contributes to the existing social capital debate at least in three respects. Firstly, it shows that measuring individuals’ social capital on the basis of associational life can be misleading. In some communities, voluntary associations may not be the most important source of social capital. Secondly, Congolese immigrants’ social capital powerlessness illustrates that social capital productivity is function not only of social interactions but also of broad institutional context. Thirdly, political engagement does not just follow from associations’ attendance. An apolitical association such as Jehovah witness church or an association attended mainly by undereducated people may still build organisational skills, but insulate participants from the political community.
Student Number : 0506739P - MA research report - School of Social Sciences - Faculty of Humanities
Keywords: Social Capital; Economic Performance; Political Engagement; Immigrants